Synthesis and Assessment of an Antimicrobial Composite Developed Using Silver Nanoparticles and Egg Shell-Activated Charcoal: Application in Water Purification - J, Nancy Paul; S, Balachandar. (Asian Journal of Biological and Life Sciences, 2024)
Aims: As filtration is one of the significant steps in the water purification process, one such filtration material was developed using nitrocellulose filter papers coated with a novel nanocomposite, in the present research, with the aim to evaluate its qualitative antibacterial efficacy and filtration efficiency. Materials and Methods: Bio-green synthesis of Silver Nanoparticles (AgNPs) using Ocimum basilicum extracts was studied along with different characterization parameters. Egg shell-activated charcoal was developed using standard methods. A nanocomposite containing silver nanoparticles and egg shell charcoal was developed and nomenclatured as SECNC. The antibacterial activity of SECNC was determined using the standard well diffusion method. Nitrocellulose filter papers were coated or impregnated with developed SECNC, and its filtration efficiency and antibacterial efficacy were evaluated. Findings: Bio-synthesis of nanoparticles was confirmed from a colourless solution to yellow brown because of the action of surface plasmon vibrations. SEM analysis of AgNPs revealed that the particles were formed as agglomerates with size ranging from 77.17 nm to 84.18 nm. The antibacterial activity of SECNC ranged from 16 mm to 19 mm for 30 μg/mL concentration. The qualitative antibacterial activity of SECNC-coated nitrocellulose filters ranged from 29 mm to 31 mm of inhibitory zones. Significant differences in the values for TDS, conductivity, and hardness were found evident between the before and after filtration process. Total plate count results also showed significant difference in CFU/mL between the before and after filtration process. Conclusion: The results revealed that water sample was efficiently filtered by the nanocomposite-coated nitrocellulose filters during the study.
Keywords: Egg Shell Charcoal; Filters; Green synthesis; Nanocomposite; Nitrocellulose; Silver nanoparticles